Time series approach to athletes motor potential - Maszczyk, A.; Roczniok, R.; Pietraszewski, P.; Stanula, A.; Zajac, A.; Golas, A. (Polish Journal of Sport and Tourism, 2012)
The aim of this study was to determine the dynamics of changes in selected motor abilities of javelin throwers and to determine predictors of javelin throw distances. Material and methods. Research material included the results obtained from a group of 60 competitors from the Silesia Region of Poland, aged 14 - 15 years. In order to answer the research question, the following statistical analysis were employed: Pearson's linear correlation coefficients, vectors R0 and R1, time series analysis, distributed lag analysis and Almon distributed lag analysis and coefficient of concordance Results. The correlation analyzes allowed for a selection of two variables for further analyses: specific strength of arms and trunk (SSAT) and specific strength of shoulders girdle and trunk (SSGT). Calculated indexes revealed that the level of SSAT showed a constant upward tendency (+15%). The highest rise in SSAT level was recorded in the 4th and 5th quarter (+9%). The level of SSGT showed an upward tendency nearly (+6%). In this case, the highest rise was observed in the 7th and 8th quarter (+4.5%). Conclusions. The standardized regression analysis revealed that the variable of specific power of arms and trunk (SOBT) is the most important predictor for javelin throw distance with a full approach run.